Titanium dioxide nanosheets vertically coated with MXene materials, electrochemical sensors and preparation methods
By preparing titanium dioxide nanosheets vertically coated MXene materials and prepared into electrochemical sensors, the problem of difficulty in detecting multiple biological small molecules at the same time is solved, and high sensitivity and high resolution biological small molecules detection is achieved.
Patent Information
- Application Number
- CN202310086634.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-02-09
AI Technical Summary
Traditional material electrodes are difficult to achieve simultaneous detection of multiple biological small molecules in electrochemical sensors, and the detection efficiency is low.
By preparing titanium dioxide nanosheets vertically coated MXene material and preparing it into an electrochemical sensor, it uses its high specific surface area and good metal conductivity to improve the detection resolution of a variety of biological small molecules.
It has achieved high sensitivity detection of small biological molecules such as dopamine, uric acid, ascorbic acid, glucose, cholesterol, and amino acids. It has low detection concentration and strong anti-interference ability, and has improved the electrochemical detection ability of biological molecules.
Smart Images

Figure CN116106378B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and specifically relates to titanium dioxide nanosheets vertically coated with MXene materials, electrochemical sensors and preparation methods. Background Art
[0002] Glucose, cholesterol, amino acids, ascorbic acid (AA), dopamine (DA) and uric acid (UA) are important biological small molecules that affect human health and skills. Abnormal glucose content in human body fluids can lead to common diseases such as hypoglycemia or diabetes; when the human body has low-density lipoprotein cholesterol, it can cause damage to the arteries, while high-density lipoprotein cholesterol can lead to reduced synthesis of corticosteroids, which can weaken stress resistance, weaken immunity, and weaken normal disease resistance; abnormal amino acids can lead to abnormal protein content in the human body, causing kidney disease or poor development in children. When the ascorbic acid content in the human body is too high, it will produce side effects such as polyuria, diarrhea, and skin rash. When the content is too low, it will cause cell connection disorders and easily cause scurvy; when the dopamine content is abnormal, it can cause involuntary muscle tremors at the mildest, and Parkinson's disease, Alzheimer's disease and other diseases at the most serious; when the uric acid in human body fluids is too high, it can lead to gout, cardiovascular disease and other diseases. Usually these substances exist simultaneously in human body fluids. Therefore, during clinical treatment, simultaneous monitoring of the concentrations of biological small molecules in the patient's body fluids plays a very important role in determining the cause of the patient's condition.
[0003] At present, electrochemical methods have gradually become the mainstream research direction due to their low detection limit, low cost and simple operation. However, when traditional material electrodes are used as electrochemical sensors, their detection peak potentials often overlap, making them only applicable to the detection of a single biological small molecule, and the detection efficiency is low. By synthesizing special nanomaterials and preparing them into electrode sensors, the detection peaks of different biological small molecules can be deviated, thereby improving the detection resolution of multiple biological small molecules, thereby achieving the simultaneous detection of multiple biological small molecules.
[0004] Two-dimensional transition metal carbides (MXene) have excellent detection sensitivity in the sensor field due to their layered structure and multiple surface functional groups, which make them hydrophilic, high specific surface area, high metal conductivity, good flexibility, etc. However, MXene-based electrode sensors are difficult to achieve simultaneous detection of multiple biological small molecules. Summary of the invention
[0005] In view of this, on the one hand, some embodiments disclose a method for preparing a titanium dioxide nanosheet vertically coated with a MXene material, comprising:
[0006] The titanium-containing reactant, the alcohol solvent and the accelerator are mixed in a set ratio to obtain a first mixed solution;
[0007] Adding a set proportion of MXene to the first mixed solution under stirring conditions to obtain a second mixed solution;
[0008] The second mixed solution is placed in a sealed container for reaction to obtain a solid powder of titanium dioxide nanosheets vertically coated with MXene;
[0009] The solid powder of titanium dioxide nanosheets vertically coated with MXene is subjected to a first annealing treatment to obtain a crystalline titanium dioxide nanosheet vertically coated with MXene material;
[0010] The crystalline titanium dioxide nanosheets vertically coated MXene material is subjected to a second annealing treatment in a set atmosphere to obtain the titanium dioxide nanosheets vertically coated MXene material with active site regulation.
[0011] Furthermore, in some embodiments of the preparation method of titanium dioxide nanosheets vertically coated with MXene materials, the alcohol solvent includes any one of ethylene glycol, propylene glycol, polyethylene glycol, and ethylene glycol butyl ether, the titanium-containing reactant includes any one of titanium trichloride, Ti(OH)4, H4TiO4, and titanium tetrachloride, and the promoter includes any one of deionized water, hydrogen peroxide, sodium percarbonate, and sodium hypochlorite; the volume ratio of the alcohol solvent, the titanium-containing reactant, and the promoter is set to 100:0.1~10:0.5~20.
[0012] Some embodiments disclose a method for preparing a titanium dioxide nanosheet vertically coated with a MXene material, wherein the MXene includes Ti2CT x 、Ti3C2T x 、Ti4N3T x 、Nb2CT x 、V2CT x Any one of , wherein T represents a functional group and x represents the number of functional groups.
[0013] In some embodiments, the preparation method of the titanium dioxide nanosheet vertically coated MXene material disclosed in the present invention comprises: placing the second mixed solution in a sealed container for reaction to obtain a solid powder of the titanium dioxide nanosheet vertically coated MXene, comprising:
[0014] Pour the second mixed solution into a high-pressure reactor, tighten the lid of the reactor and place it in a heating box;
[0015] Let stand at 10-40℃ for 1-20 hours;
[0016] Heating to 100-130°C and keeping at this temperature for 1-20 hours;
[0017] Raise the temperature to 150-180°C and keep warm for 1-20 hours;
[0018] The mixture was cooled to room temperature, and the obtained mixed solution was separated. The obtained solid powder was washed and dried to obtain a solid powder in which titanium dioxide nanosheets vertically coated MXene.
[0019] In the preparation method of the titanium dioxide nanosheet vertically coated MXene material disclosed in some embodiments, the first annealing comprises:
[0020] The solid powder of MXene vertically coated with titanium dioxide nanosheets is first heated to 100-120°C in an argon atmosphere for 1-2 hours;
[0021] Then the temperature is raised to 280-900°C and kept warm for 1-10 hours to obtain a MXene material vertically coated with titanium dioxide crystals; wherein, the temperature is kept warm at 280-400°C to obtain anatase-type titanium dioxide-coated MXene material; the temperature is kept warm at 500-650°C to obtain a rutile-type titanium dioxide-coated MXene material; the temperature is kept warm at 700-900°C to obtain a rutile-type titanium dioxide-coated titanium carbide composite.
[0022] In the preparation method of the titanium dioxide nanosheet vertically coated MXene material disclosed in some embodiments, the second annealing comprises:
[0023] The crystalline titanium dioxide nanosheets vertically coated MXene material was put back into the atmosphere-controlled heating box, and kept warm for 5 to 100 minutes at the set temperature in the atmospheres of oxygen-argon mixed gas, nitrogen-argon mixed gas, and hydrogen-argon mixed gas, respectively, to obtain oxygen-doped titanium dioxide nanosheets vertically coated MXene material, nitrogen-doped crystalline titanium dioxide nanosheets vertically coated MXene material, and pure crystalline titanium dioxide nanosheets vertically coated MXene material, respectively.
[0024] On the other hand, some embodiments disclose an electrochemical sensor, including an active site-regulated titanium dioxide nanosheet vertically coated MXene material obtained by a preparation method of a titanium dioxide nanosheet vertically coated MXene material.
[0025] In another aspect, some embodiments disclose a method for preparing an electrochemical sensor, which is used to prepare an electrochemical sensor, comprising:
[0026] The active site-regulated titanium dioxide nanosheet vertically coated MXene material is dissolved and dispersed in anhydrous ethanol to obtain a dispersed suspension of the active site-regulated titanium dioxide nanosheet vertically coated MXene material;
[0027] The dispersed suspension droplets of active site-regulated titanium dioxide nanosheets vertically coated with MXene material are applied to the surface of the glassy carbon electrode, and then dried to obtain the active site-regulated titanium dioxide nanosheets vertically coated with MXene material coated glassy carbon electrode.
[0028] Furthermore, the electrochemical sensor preparation method disclosed in some embodiments also includes an electrochemical activation step of vertically coating the active site-regulated titanium dioxide nanosheet with the MXene material coated glassy carbon electrode, specifically including:
[0029] Cyclic voltammetry was performed at a scan rate of 50 mV·s between the potentials of -0.1 and -0.6 V. -1 The glassy carbon electrode coated with MXene material vertically coated with titanium dioxide nanosheets with active site regulation was cyclically scanned in a 0.1 M phosphate buffer solution to obtain an electrochemical sensor based on active site regulated titanium dioxide nanosheets vertically coated with MXene material.
[0030] In another aspect, some embodiments disclose the use of electrochemical sensors in detecting biological small molecules.
[0031] The preparation method of the titanium dioxide nanosheet vertically coated MXene material disclosed in the embodiment of the present invention obtains the titanium dioxide nanosheet vertically coated MXene material, and further prepares the titanium dioxide nanosheet vertically coated MXene material into an electrochemical sensor, which can perform electrochemical detection of small biological molecules, for example, it can detect dopamine, uric acid, ascorbic acid, glucose, cholesterol, amino acids, etc., with low detection concentration, high detection sensitivity, strong anti-interference ability, and good application prospects in the field of electrochemical detection of biological molecules. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 SEM images of titanium dioxide nanosheets vertically coated with MXene materials disclosed in some embodiments;
[0033] Figure 2 DPV detection of AA, DA and UA by the titanium dioxide nanosheets vertically coated with MXene modified glassy carbon electrode disclosed in some embodiments and the linear relationship diagram;
[0034] Figure 3 Differential pulse voltammetry curves and linear relationship diagrams of the simultaneous detection of AA, DA and UA by the glassy carbon electrode modified with MXene vertically coated with titanium dioxide nanosheets disclosed in some embodiments;
[0035] Figure 4 Repeatability test curves and stability test curves of the titanium dioxide nanosheets vertically coated with MXene-modified glassy carbon electrodes disclosed in some embodiments. DETAILED DESCRIPTION
[0036] The word "embodiment" used herein as an "exemplary" does not necessarily mean that any embodiment described is superior or better than other embodiments. Performance index tests in the embodiments of the present invention are performed using conventional test methods in the art unless otherwise specified. It should be understood that the terms described in the embodiments of the present invention are only used to describe specific implementation methods and are not intended to limit the contents disclosed in the embodiments of the present invention.
[0037] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the embodiments of the present invention belong; other experimental methods and technical means not specifically specified in the embodiments of the present invention refer to experimental methods and technical means commonly used by ordinary technicians in the field.
[0038] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values clearly listed as the limits of the range, but also all independent values or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values of 1% to 5%, but also the independent values and sub-ranges within the range shown. Therefore, independent values such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described.
[0039] In this document, including in the claims, transitional words such as "comprises," "includes," "with," "having," "containing," "involving," "accommodating," etc. are understood to be open-ended, i.e., meaning "including but not limited to." Only the transitional words "consisting of" and "composed of" are closed transitional words.
[0040] In order to better illustrate the present invention, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the gist of the present invention.
[0041] Under the premise of no conflict, the technical features disclosed in the embodiments of the present invention may be arbitrarily combined, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present invention.
[0042] In some embodiments, the method for preparing a titanium dioxide nanosheet vertically coated with a MXene material comprises:
[0043] The titanium-containing reactant, the alcohol solvent and the accelerator are mixed in a set ratio to obtain a first mixed solution;
[0044] Adding a set proportion of MXene to the first mixed solution under stirring conditions to obtain a second mixed solution;
[0045] The second mixed solution is placed in a sealed container for reaction to obtain a solid powder of titanium dioxide nanosheets vertically coated with MXene;
[0046] The solid powder of titanium dioxide nanosheets vertically coated with MXene is subjected to a first annealing treatment to obtain a crystalline titanium dioxide nanosheet vertically coated with MXene material;
[0047] The crystalline titanium dioxide nanosheets vertically coated MXene material is subjected to a second annealing treatment in a set atmosphere to obtain the titanium dioxide nanosheets vertically coated MXene material with active site regulation.
[0048] In some embodiments, the alcohol solvent includes any one of ethylene glycol, propylene glycol, polyethylene glycol, and ethylene glycol butyl ether, the titanium-containing reactant includes any one of titanium trichloride, Ti(OH)4, H4TiO4, and titanium tetrachloride, and the promoter includes any one of deionized water, hydrogen peroxide, sodium percarbonate, and sodium hypochlorite; the volume ratio of the alcohol solvent, the titanium-containing reactant, and the promoter is set to 100:0.1~10:0.5~20.
[0049] In some embodiments, the MXene includes Ti2CT x 、Ti3C2T x 、Ti4N3T x 、Nb2CT x 、V2CT x Any one of , wherein T represents a functional group and x represents the number of functional groups.
[0050] In some embodiments, under magnetic stirring conditions, the alcohol solvent, the titanium-containing reactant and the promoter are mixed in a volume ratio of 100:0.1-10:0.5-20, and the first mixed solution is obtained after mixing evenly.
[0051] In some embodiments, under magnetic stirring conditions, MXene is slowly added to the first mixed solution, and mixed evenly to obtain a second mixed solution. x 、Ti3C2T x 、Ti4N3T x 、Nb2CT x 、V2CT xAny one of the above; the morphology of MXene is usually accordion-shaped, few-layered or single-layered; the second mixed solution can usually be ultrasonically treated for an appropriate time to make the MXene uniformly dispersed in the second mixed solution.
[0052] In some embodiments, the second mixed solution is placed in a sealed container for reaction to obtain a solid powder of titanium dioxide nanosheets vertically coated with MXene, including:
[0053] Pour the second mixed solution into a high-pressure reactor, tighten the lid of the reactor and place it in a heating box;
[0054] First, let it stand at 10-40°C for 1-20 hours;
[0055] Then heat to 100-130°C and keep at this temperature for 1-20 hours;
[0056] Then continue to raise the temperature to 150-180°C and keep it at 150-180°C for 1-20 hours;
[0057] Finally, cool to room temperature; separate the obtained mixed solution, wash and dry the obtained solid powder, and obtain solid powder of titanium dioxide nanosheets vertically coated with MXene. For example, the mixed solution can be centrifuged, and then the solid powder obtained by centrifugation can be centrifugally washed 3-4 times with anhydrous ethanol, and then the washed solid powder can be placed in a vacuum chamber for drying. After drying for 1-2 days, a solid powder of dried titanium dioxide nanosheets uniformly and vertically coated on the surface of MXene can be obtained.
[0058] In some embodiments, a solid powder in which titanium dioxide nanosheets are uniformly and vertically coated on the surface of MXene is subjected to a first annealing treatment to adjust its physical phase. Usually, the solid powder is cooled to room temperature after annealing to obtain a product. For example, the first annealing process includes:
[0059] The solid powder of MXene vertically coated with titanium dioxide nanosheets is first heated to 100-120°C in an argon atmosphere for 1-2 hours;
[0060] The temperature is then raised to 280-900°C and kept warm for 1-10 hours to obtain a MXene material vertically coated with titanium dioxide crystals; usually annealing at different temperatures can obtain MXene composites coated with titanium dioxide of different crystal forms.
[0061] In some embodiments, the temperature is kept at 280-400° C. to obtain anatase-type titanium dioxide-coated MXene material.
[0062] In some embodiments, the temperature is kept at 500-650° C. to obtain a rutile titanium dioxide-coated MXene material.
[0063] In some embodiments, the temperature is kept at 700-900° C. to obtain a rutile titanium dioxide-coated titanium carbide composite.
[0064] In some embodiments, the titanium dioxide-coated MXene composite that has undergone the first annealing treatment is subjected to a second annealing treatment, so as to adjust the composition of the product by adjusting the gas composition, ratio, annealing time, etc. in the annealing atmosphere; for example, the second annealing process includes:
[0065] The crystalline titanium dioxide nanosheet vertically coated MXene material is put back into the atmosphere-controlled heating box, and kept warm in the atmospheres of oxygen-argon mixed gas, nitrogen-argon mixed gas, and hydrogen-argon mixed gas at a set temperature for 5 to 100 minutes, to obtain oxygen-doped oxygen-doped crystalline titanium dioxide nanosheet vertically coated MXene material, nitrogen-doped crystalline titanium dioxide nanosheet vertically coated MXene material, and pure crystalline titanium dioxide nanosheet vertically coated MXene material, respectively.
[0066] In some embodiments, for anatase titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in an oxygen-argon mixed atmosphere at an annealing temperature of 200 to 400° C. The annealing time is 5 to 100 minutes to obtain oxygen-doped anatase titanium dioxide nanosheets vertically coated with MXene, i.e., oxygen-doped anatase vTiO2NPs@MXene, wherein the volume ratio of oxygen to argon in the oxygen-argon mixed atmosphere is 1:0.1 to 10.
[0067] In some embodiments, for anatase titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in a nitrogen-argon mixed atmosphere at an annealing temperature of 200 to 400° C. The annealing time is 5 to 100 minutes to obtain nitrogen-doped anatase titanium dioxide nanosheets vertically coated with MXene, i.e., nitrogen-doped anatase vTiO2NPs@MXene, wherein the volume ratio of nitrogen to argon in the nitrogen-argon mixed atmosphere is 1:0.1 to 10.
[0068] In some embodiments, for anatase titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in a hydrogen-argon mixed atmosphere at an annealing temperature of 200 to 400° C. The annealing time is 5 to 100 minutes to obtain pure anatase titanium dioxide nanosheets vertically coated with MXene, i.e., pure anatase vTiO2NPs@MXene, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixed atmosphere is 1:0.1 to 10.
[0069] In some embodiments, for rutile titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in an oxygen-argon mixed atmosphere at an annealing temperature of 500-600°C for a time of 5-100 minutes to obtain oxygen-doped rutile titanium dioxide nanosheets vertically coated MXene, i.e., oxygen-doped rutile vTiO2NPs@MXene, wherein the volume ratio of oxygen to argon in the oxygen-argon mixed atmosphere is 1:0.1-10.
[0070] In some embodiments, for rutile titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in a nitrogen-argon mixed atmosphere at an annealing temperature of 500-600°C for 5-100 minutes to obtain nitrogen-doped rutile titanium dioxide nanosheets vertically coated with MXene, i.e., nitrogen-doped rutile vTiO2NPs@MXene, wherein the volume ratio of nitrogen to argon in the nitrogen-argon mixed atmosphere is 1:0.1-10.
[0071] In some embodiments, for rutile titanium dioxide-coated MXene, a heat preservation annealing treatment is carried out in a hydrogen-argon mixed atmosphere at an annealing temperature of 500-600°C for a time of 5-100 minutes to obtain pure rutile titanium dioxide nanosheets vertically coated with MXene, i.e., pure rutile vTiO2NPs@MXene, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixed atmosphere is 1:0.1-10.
[0072] In some embodiments, for the rutile titanium dioxide coated titanium carbide composite, a heat preservation annealing treatment is carried out in an oxygen-argon mixed atmosphere at an annealing temperature of 700-800°C for an annealing time of 5-100 minutes to obtain oxygen-doped rutile titanium dioxide nanosheets vertically coated with titanium carbide, i.e., oxygen-doped rutile vTiO2NPs@MXene, wherein the volume ratio of oxygen to argon in the oxygen-argon mixed atmosphere is 1:0.1-10.
[0073] In some embodiments, for the rutile titanium dioxide coated titanium carbide composite, a heat preservation annealing treatment is carried out in a nitrogen and argon mixed atmosphere at an annealing temperature of 700-800°C for a time of 5-100 minutes to obtain nitrogen-doped rutile titanium dioxide nanosheets vertically coated with titanium carbide, i.e., nitrogen-doped rutile vTiO2NPs@MXene, wherein the volume ratio of nitrogen to argon in the nitrogen and argon mixed atmosphere is 1:0.1-10.
[0074] In some embodiments, for the rutile titanium dioxide coated titanium carbide composite, a heat preservation annealing treatment is carried out in a hydrogen and argon mixed atmosphere at an annealing temperature of 700-800°C for an annealing time of 5-100 minutes to obtain pure rutile titanium dioxide nanosheets vertically coated with titanium carbide, i.e., pure rutile vTiO2NPs@MXene, wherein the volume ratio of hydrogen to argon in the hydrogen and argon mixed atmosphere is 1:0.1-10.
[0075] In some embodiments, the electrochemical sensor includes an active site-regulated titanium dioxide nanosheet vertically coated MXene material obtained by a preparation method of a titanium dioxide nanosheet vertically coated MXene material.
[0076] In some embodiments, the preparation method of the electrochemical sensor includes:
[0077] The active site-regulated titanium dioxide nanosheet vertically coated MXene material is dissolved and dispersed in anhydrous ethanol to obtain a dispersed suspension of the active site-regulated titanium dioxide nanosheet vertically coated MXene material;
[0078] The active site-regulated titanium dioxide nanosheets vertically coated with MXene material dispersed suspension droplets are applied to the surface of the glassy carbon electrode, and dried to obtain the active site-regulated titanium dioxide nanosheets vertically coated with MXene material coated glassy carbon electrode. Figure 1 As shown, it is a scanning electron microscope (SEM) image of titanium dioxide nanosheets vertically coating MXene materials. A large number of titanium dioxide nanosheets are distributed on the surface of the multilayer structure of MXene, coating the surface of the layers in the layered structure of MXene, wherein the titanium dioxide nanosheets are perpendicular to the surface of the layer structure in MXene.
[0079] In some embodiments, the electrochemical sensor preparation method further includes the step of electrochemically activating the active site-regulated titanium dioxide nanosheet vertically coated with MXene material coated glassy carbon electrode, specifically comprising: using cyclic voltammetry, at a potential between -0.1 and -0.6 V, with a scan rate of 50 mV·s -1 The glassy carbon electrode coated with MXene material vertically coated with titanium dioxide nanosheets with active site regulation was cyclically scanned in 0.1M phosphate buffer solution to obtain an electrochemical sensor based on active site regulation of titanium dioxide nanosheets vertically coated with MXene material.
[0080] In some embodiments, anatase titanium dioxide-coated MXene black powder, i.e., vTiO2NPs@MXene, is dissolved and dispersed in anhydrous ethanol to obtain a vTiO2NPs@MXene dispersed suspension; a glassy carbon electrode GCE is polished, cleaned, and dried, and then the vTiO2NPs@MXene dispersed suspension is dropwise coated on the surface of the glassy carbon electrode GCE and dried to obtain anatase titanium dioxide-coated MXene-coated glassy carbon electrode, i.e., vTiO2NPs@MXene / GCE; and then cyclic voltammetry is used at a potential between -0.1 and -0.6 V with a scan rate of 50 mV·s -1 , and scanned 20 times in a 0.1 M PBS solution to obtain the electrochemical sensor vTiO2NPs@MXene / GCE.
[0081] Generally, the electrochemical sensor vTiO2NPs@MXene / GCE can be used as a working component to respond to biological molecules under certain conditions. The biological molecules undergo electrochemical reactions on the working component to generate electrical signals, thereby realizing electrochemical detection of the biological molecules.
[0082] In some embodiments, the use of electrochemical sensors in detecting biological small molecules is disclosed.
[0083] In some embodiments, the electrochemical sensor anatase vTiO2NPs@MXene / GCE is used as the working electrode, the platinum electrode is used as the counter electrode, and the saturated silver chloride is used as the reference electrode. The sensor is placed in a phosphate buffer solution with a pH of 7.4 and a concentration of 0.1M. The scanning point is set to -0.2 to 0.6V. Under the differential pulse condition, the amplitude is 0.05V, the pulse period is 0.5s, and the pulse width is 0.05s. The scanning test is performed to record the differential pulse voltammetry curve of the biomolecule on the vTiO2NPs@MXene / GCE electrode, and a linear relationship between the concentration of the biomolecule and the current can be obtained. Figure 2 As shown in the figure, the glassy carbon electrode modified with MXene vertically coated with anatase titanium dioxide was used as the working electrode, and DPV detection of ascorbic acid AA, dopamine DA and uric acid UA was performed separately. The results showed that as shown in the figure (a), the detection range of AA was 40-300 μM, and as shown in the figure (d), the linear relationship was good within the detection range, and the linear correlation R 2 The detection limit is 0.19 μM. As shown in (b), the detection range of DA is 50-400 μM. As shown in (e), the linear relationship is good. The linear correlation R 2 is 0.9941, and the detection limit is 0.25 μM; as shown in Figure (c), the detection range of UA is 50-600 μM, as shown in Figure (f), the linear relationship is good, and the linear correlation R 2The detection limit was 0.9975 and 2.91 μM.
[0084] Generally, the sensitivity of detection of different biological small molecules can be adjusted by adjusting the physical phase and composition of the titanium dioxide nanosheets vertically coated with MXene materials in electrochemical sensors, such as the doping ratio. For example, anatase vTiO2NPs@MXene can simultaneously detect three small molecules, dopamine, uric acid, or ascorbic acid, with high sensitivity at appropriate oxygen doping concentrations, and has no reaction to other biological small molecules.
[0085] In some embodiments, the oxygen-doped anatase vTiO2NPs@MXene / GCE is used as the working electrode, the platinum electrode is used as the counter electrode, and the saturated silver chloride is used as the reference electrode. The electrodes are placed in a phosphate buffer solution with a pH of 7.4 and a concentration of 0.1M. The scanning point is set to -0.2 to 0.6V. Under differential pulse conditions, the amplitude is 0.05V, the pulse period is 0.5s, and the pulse width is 0.05s. The scanning test is performed to detect dopamine, uric acid, and ascorbic acid at the same time. The linear ranges are 40 to 300μM, 50 to 400μM, and 200 to 1000μM, respectively, and the detection limits are 0.19μM, 0.25μM, and 2.91μM, respectively. Figure 3 As shown in the figure, when the oxygen-doped anatase vTiO2NPs@MXene electrochemical sensor detects dopamine, uric acid and ascorbic acid simultaneously, corresponding peaks can appear for AA, DA and UA at different scanning potentials, indicating that AA, DA and UA can be detected simultaneously. Among them, the response peak for AA appears near the potential of 0.08V, as shown in (a), and the detectable range is 200-1000μM. As shown in (b), the linear relationship is good, and the correlation factor R 2 is 0.9875; near the potential of 0.25 V, a response peak to DA appears, and the detectable range is 40 to 300 μM, as shown in Figure (c), with good linear correlation and a correlation factor R 2 is 0.9875; near the potential of 0.46 V, a response peak to UA appears, and the detectable range is 50-400 μM, as shown in (d) in the figure, with good linear correlation and correlation factor R 2 is 0.9991.
[0086] In the example of detecting ascorbic acid, 200 μM ascorbic acid, 40 μM dopamine and 60 μM uric acid were measured five times in succession. According to the experimental results, the relative standard deviation RSD was 0.54%. Further, the electrochemical sensor was placed in the air for 5 days and then subjected to differential micropulse voltammetry test, i.e., DPV test. The test results are shown in FIG. Figure 4 As shown, the current has basically not changed, indicating that when interfering substances are added, it does not affect the detection current, indicating that the electrode has a strong anti-interference ability.
[0087] In some embodiments, rutile vTiO2NPs@MXene can detect glucose and cholesterol separately at appropriate nitrogen doping concentrations, and has no response to other biological small molecules.
[0088] In some embodiments, pure anatase vTiO2NPs@MXene can realize the separate detection of amino acids, glutamic acid and lysine, and has no reaction to other biological small molecules.
[0089] Generally, MXene nanosheets can be prepared by commonly used methods in the art. For example, MAX material is etched with hydrofluoric acid and then ultrasonically treated to obtain MXene material, and the obtained MXene material is further ultrasonically dispersed with ethylene glycol to obtain MXene nanosheets.
[0090] The preparation method of the titanium dioxide nanosheet vertically coated MXene material disclosed in the embodiment of the present invention obtains the titanium dioxide nanosheet vertically coated MXene material, and further prepares the titanium dioxide nanosheet vertically coated MXene material into an electrochemical sensor, which can perform electrochemical detection of small biological molecules, for example, it can detect dopamine, uric acid, ascorbic acid, etc., with low detection concentration, high detection sensitivity, strong anti-interference ability, and has good application prospects in the field of electrochemical detection of biological molecules.
[0091] The technical solutions disclosed in the embodiments of the present invention and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of the present invention and do not constitute a limitation on the technical solutions of the embodiments of the present invention. Any conventional changes, replacements or combinations of the technical details disclosed in the embodiments of the present invention have the same inventive concept as the present invention and are within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a MXene material vertically coated with titanium dioxide nanosheets, characterized in that: include: The titanium-containing reactant, alcohol solvent and promoter are mixed in a set ratio to obtain a first mixed solution; wherein the titanium-containing reactant includes titanium trichloride, Ti(OH) 4、 Any one of H4TiO4 and titanium tetrachloride, the promoter includes any one of deionized water, hydrogen peroxide, sodium percarbonate and sodium hypochlorite; the volume ratio of the alcohol solvent, the titanium-containing reactant and the promoter is set to 100:0.1-10:0.5-20; Adding a set proportion of MXene to the first mixed solution under stirring conditions to obtain a second mixed solution; The second mixed solution is placed in a sealed container for reaction to obtain a solid powder of titanium dioxide nanosheets vertically coated with MXene; specifically comprising: pouring the second mixed solution into a high-pressure reactor, tightening the reactor cover and placing it in a heating box; standing at 10 to 40°C for 1 to 20 hours; heating to 100 to 130°C and keeping the temperature at this temperature for 1 to 20 hours; heating to 150 to 180°C and keeping the temperature for 1 to 20 hours; cooling to room temperature, separating the obtained mixed solution, washing and drying the obtained solid powder, and obtaining a solid powder of titanium dioxide nanosheets vertically coated with MXene; The solid powder of MXene vertically coated with titanium dioxide nanosheets is subjected to a first annealing treatment to obtain a MXene material vertically coated with crystalline titanium dioxide nanosheets; the first annealing comprises: firstly heating the solid powder of MXene vertically coated with titanium dioxide nanosheets to 100-120°C under an argon atmosphere for 1-2 hours; then heating to 280-900°C for 1-10 hours to obtain a MXene material vertically coated with titanium dioxide crystals; wherein, the MXene material coated with anatase titanium dioxide is obtained by heating at 280-400°C; the MXene material coated with rutile titanium dioxide is obtained by heating at 500-650°C; and the composite material coated with titanium carbide is obtained by heating at 700-900°C; The crystalline titanium dioxide nanosheet vertically coated MXene material is subjected to a second annealing treatment in a set atmosphere to obtain an active site-regulated titanium dioxide nanosheet vertically coated MXene material; the second annealing comprises: placing the crystalline titanium dioxide nanosheet vertically coated MXene material back into an atmosphere-controllable heating box, and keeping it warm for 5 to 100 minutes at a set temperature in an oxygen-argon mixed gas, a nitrogen-argon mixed gas, and a hydrogen-argon mixed gas atmosphere, respectively, to obtain an oxygen-doped crystalline titanium dioxide nanosheet vertically coated MXene material, a nitrogen-doped crystalline titanium dioxide nanosheet vertically coated MXene material, and a pure crystalline titanium dioxide nanosheet vertically coated MXene material, respectively.
2. The method for preparing a MXene material vertically coated with titanium dioxide nanosheets according to claim 1, characterized in that: The alcohol solvent includes any one of ethylene glycol, propylene glycol, polyethylene glycol, and ethylene glycol butyl ether.
3. The method for preparing a MXene material vertically coated with titanium dioxide nanosheets according to claim 1, characterized in that: The MXene includes Ti2CT x 、Ti3C2T x 、Ti4N3T x 、Nb2CT x 、V2CT x Any one of , wherein T represents a functional group and x represents the number of functional groups.
4. An electrochemical sensor, characterized in that The invention relates to a titanium dioxide nanosheet vertically coated MXene material with active site regulation obtained by the preparation method of the titanium dioxide nanosheet vertically coated MXene material according to any one of claims 1 to 3.
5. A method for preparing an electrochemical sensor, characterized in that: For preparing the electrochemical sensor according to claim 4, comprising: The active site-regulated titanium dioxide nanosheet vertically coated MXene material is dissolved and dispersed in anhydrous ethanol to obtain a dispersed suspension of the active site-regulated titanium dioxide nanosheet vertically coated MXene material; The dispersed suspension droplets of active site-regulated titanium dioxide nanosheets vertically coated with MXene material are applied to the surface of the glassy carbon electrode, and then dried to obtain the active site-regulated titanium dioxide nanosheets vertically coated with MXene material coated glassy carbon electrode.
6. The method for preparing an electrochemical sensor according to claim 5, characterized in that: It also includes the electrochemical activation steps of the active site-regulated titanium dioxide nanosheets vertically coated with MXene material coated glassy carbon electrodes, specifically including: Cyclic voltammetry was performed at a scan rate of 50 mV·s between the potentials of -0.1 and -0.6 V. -1 The glassy carbon electrode coated with MXene material vertically coated with titanium dioxide nanosheets with active site regulation was cyclically scanned in a 0.1M phosphate buffer solution to obtain an electrochemical sensor based on active site regulated titanium dioxide nanosheets vertically coated with MXene material.
7. Use of the electrochemical sensor according to claim 4 in detecting biological small molecules.
Citation Information
Patent Citations
Nitrogen-doped rod-like titanium oxide / two-dimensional laminated titanium carbide nanometer composite electrode material, and preparation method and application therefor
CN106024416A
Application of electrochemical sensor containing VO-titanium dioxide-coated MXene composite material in detection of imidacloprid
CN115656286A